2009
DOI: 10.1039/b900553f
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of ferric ions in the presence of sulfate or chloride ions: implications for the photo-Fenton process

Abstract: The photo-Fenton process (Fe(2+)/Fe(3+), H(2)O(2), UV light) is one of the most efficient and advanced oxidation processes for the mineralization of the organic pollutants of industrial effluents and wastewater. The overall rate of the photo-Fenton process is controlled by the rate of the photolytic step that converts Fe(3+) back to Fe(2+). In this paper, the effect of sulfate or chloride ions on the net yield of Fe(2+) during the photolysis of Fe(3+) has been investigated in aqueous solution at pH 3.0 and 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 33 publications
1
49
0
2
Order By: Relevance
“…For this purpose, one must include additional kinetic steps that are too slow to be relevant on the time scale of the laser flash photolysis experiments. Experimentally (Machulek et al, 2009b) it is found that the concentration of Fe 2+ eventually reaches a plateau value at long times, more quickly in the presence of chloride ion than in its absence ( Figure 6). Simulation of this behavior required the inclusion of additional kinetic steps, in particular for the back reactions that result in reoxidation of Fe 2+ .…”
Section: Wwwintechopencom Organic Pollutants Ten Years After the Stmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, one must include additional kinetic steps that are too slow to be relevant on the time scale of the laser flash photolysis experiments. Experimentally (Machulek et al, 2009b) it is found that the concentration of Fe 2+ eventually reaches a plateau value at long times, more quickly in the presence of chloride ion than in its absence ( Figure 6). Simulation of this behavior required the inclusion of additional kinetic steps, in particular for the back reactions that result in reoxidation of Fe 2+ .…”
Section: Wwwintechopencom Organic Pollutants Ten Years After the Stmentioning
confidence: 99%
“…Table 2. Set of additional ground state reactions required to fit the accumulation of Fe 2+ during the steady-state irradiation of Fe 3+ in the presence and absence of chloride ion (Machulek et al, 2009b) …”
Section: Wwwintechopencom Organic Pollutants Ten Years After the Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Further the generated ferrous ions reacts with hydrogen peroxide forming ferric ions and hydroxyl radicals as discussed previously (Eqs. (7) and (10)) [24,25]. The various possible reactions that can take place between chloride and Fe 3+ ions are shown below:…”
Section: Effect Of Inorganic Salts (Chloride and Sulfate) On The Degrmentioning
confidence: 99%
“…At pH 3.0, FeSO 4 + and Fe (OH) 2+ are the major predominant ferric species present. On irradiation with UV light FeSO 4 + produces ferrous ions and sulfate anions whose quantum yield is quite low [23,24].…”
Section: Effect Of Inorganic Salts (Chloride and Sulfate) On The Degrmentioning
confidence: 99%